Proceedings of the International Congress on Information and Communication Technology ICICT 2015, Volume 2 - Satapathy, Suresh Chandra; Bhatt, Yogesh Chandra; Joshi, Amit; Mishra, Durgesh Kumar (Advances in Intelligent Systems and Computing, 2016)
This volume contains 69 papers presented at ICICT 2015: International Congress on Information and Communication Technology. The conference was held during 9th and 10th October, 2015, Udaipur, India and organized by CSI Udaipur Chapter, Division IV, SIG-WNS, SIG-e-Agriculture in association with ACM Udaipur Professional Chapter, The Institution of Engineers (India), Udaipur Local Centre and Mining Engineers Association of India, Rajasthan Udaipur Chapter. This volume contains papers mainly focused on ICT for Managerial Applications, E-governance, IOT and e-Mining.